Extensive intraductal component positive carcinoma of breast: two year study with special reference to ER/PR/HER2NEU/Ki67 in a tertiary care centre of Barak Valley - Choudhury, Madhusmita; Deka, Monoj K.; Talukdar, Anuradha; Khakhlari, Nitu M.; Chaubey, Jyoti (International Journal of Research in Medical Sciences, 2020)
Background: Extensive intraductal component positive carcinoma (EICPC) of breast is defined by Schnitt et al as- A. 25% or more of Ductal carcinoma in situ (DCIS) is present along the invasive lesion and DCIS is also present outside the area of invasive carcinoma. B. EICPC also include carcinomas in which DCIS is associated with a “small” (approximately 10 mm or less) invasive carcinoma or carcinomas. In Extensive Intraductal Carcinoma (EIDC) most of the cases were associated with recurrence when surgical margin status is not evaluated or focally involved. Our objective was to study the prevalence of EIDC and expression of estrogen receptor (ER)/progesterone receptor (PR)/human epidermal growth factor (HER2NEU)/Ki67(antigen identified by monoclonal antibody KI67) in those cases. Methods: It was a retrospective cross sectional study conducted over a period of 2017 to August 2019.All the histologically confirmed cases of EIDC was retrieved from the institute. Results: Out of 65 cases of invasive carcinoma 17 (26.1%) cases were positive for EICPC. Age of patients ranged from 27 to 73years with mean age of 43 years and 5 patients (29.4%) were postmenopausal. Most of the cases i.e. 6(35.2%) had a ER+/PR+/HER2NEU- status with most of the cases having high 6(47%)Ki-67 index. According to the BLOOM RICHARDSON GRADING 14 cases were grade II (82.3%) and 3 cases were grade I (17.7%) and in pT and pN staging majority were stage pT1 - 7 (41.1%). Most of the cases were mastectomy cases 11 (64.4%) with a base free status except in one lumpectomy case where margin was involved. Conclusions: In this study majority of the cases were ER+//PR+/HER2NEU- with most of the cases having high Ki67 index. Evaluation of EIDC, along with the negative margin status is important to prevent recurrence.